Transgenic soybean overexpressing GmNAC085 enhanced expression of important genes under salinity stress condition - Hoang Phuong Van, Pham; Dang Minh Trang, Le; Nguyen Chuong, Nguyen; Phuong Thao, Nguyen; Thi Lan Xuan, Hoang (Vietnam Journal of Biotechnology, 2020)
Climate change has made abiotic stresses such as drought and salinity bigger threats to ecosystem and global food security. In response to unfavorable conditions, physiological, biochemical and molecular activities in plants are altered. Particularly, various members of NAC (NAM, ATAF1/2, CUC2) transcriptional factor family have been reported to be the key regulators in modulating multiple biological processes of plant responses to osmotic stress conditions caused by drought and salinity. Previously, transgenic studies have shown the positive regulatory role of GmNAC085, a NAC transcription factor from soybean (Glycine max), in plant resistance against drought stress. Therefore, in this study, we extended the investigation on its contribution to salinity stress. According to our RT-qPCR analyses, expression of several important stress-related genes was significantly induced in the transgenic soybean plants in comparison with the wild-type plants, including antioxidant enzyme-encoding genes (GmSOD, GmAPX and GmCAT), sodium-proton antiporter encoding gene (GmNHX1) and proline metabolic gene (GmP5CS). Furthermore, biochemical results were also in agreement with the molecular data, with enhanced antioxidant enzyme activities of peroxidase and catalase, and in couple with lower cellular content of the reactive oxygen species hydrogen peroxide in the transgenic plants. Taken these altogether, the transgenic plants might acquire advantages in dealing with oxidative stress using enzymes and proline, as well as cellular Na+ removal under salinity stress conditions. Therefore, underlying mechanisms of GmNAC085 associated with salinity stress should be fully elaborated to find out its potential utility in crop improvement.